MANAJEMEN WAKTU, KETERAMPILAN KOMUNIKASI, SERTA PENGENDALIAN KELAS DALAM MENUNJANG DISIPLIN GURU PADA PROSES MENGAJAR - Eli Masnawati; Didit Darmawan (Universitas Islam Negeri Sumatera Utara Medan, 2026)
This study analyzes the influence of time management, communication skills, and classroom control on teacher discipline in teaching high school students in Sidoarjo City. By applying a quantitative survey method to 100 respondents selected through purposive sampling in four private schools, this study identifies three main factors that are considered to have a significant influence on the level of teacher discipline. The research instruments passed validity and reliability tests, strengthening the analysis results obtained. Based on the results of multiple linear regression, the three independent variables had a significant positive influence, with classroom control emerging as the most dominant factor in improving teaching discipline, followed by time management and communication skills. These findings indicate that efforts to strengthen teacher discipline require simultaneous improvements in competence in these three main aspects. The results show that 39.8% of the variation in teacher discipline levels can be explained by time management, communication skills, and classroom control, while the rest is triggered by other factors outside this model. The practical contribution of this study lies in its recommendations for classroom management training, strengthening time management skills, and developing effective communication programs for teachers. In addition to individual aspects, institutional support in the form of supervision, workshops, and mentoring is key to creating disciplined and high-quality teaching practices. The implications of this study direct schools and policymakers to develop teacher professionalism as a foundation for improving the quality of learning. Expanding the variables for further research is expected to provide a more complete picture of other factors that influence teacher discipline